THE EFFECT OF INFORMATIONAL GAP ACTIVITY TO THE UNMOTIVATED STUDENTS’ ABILITY OF 8th GRADERS AT MTS AL HASANAH 1 SLAHUNG, PONOROGO (RETAIN, 2014)
THE EFFECT OF INFORMATIONAL GAP ACTIVITY TO THE UNMOTIVATED STUDENTS’ ABILITY OF 8th GRADERS AT MTS AL HASANAH 1 SLAHUNG, PONOROGO Diyan Novika English Education Department, Language and Art Faculty, Surabaya State University. ndidy71@gmail.com Drs Fahri, M.A English Education Department, Language and Art Faculty, Surabaya State University. fahri@englishunesa.com Abstract The aims of this research is to find out the improvement of unmotivated students’ speaking ability after treating by using Informational Gap Activity in teaching English of the eight grader of Mts Al Hasanah 1 Slahung Ponorogo. The method that is used in this study is a quantitative method. This design of study had more potential threat to internal validity as the time between pretest and posttest increases and as experimental situation become less controlled and contrived (Mc Millan, 1992 : 175) the design of single group of pretest and posttest. The data on students’ English speaking ability were collected with a performance test. The hypothesis were tested with two-ways analysis using statistic calculation of T-test formula with significance degree 5% and 1%. And the other one is using questionnaire. The results of analysis showed that: (1) there were differences of the English speaking ability between the unmotivated students who learned through and that of the unmotivated students who learned through conventional method The result is 2,045 < 7,389 > 2,756 (2) and the other one is from their responses based on the questionnaire. The conclusion is that the implementation of Informational Gap Activity method has an effect on the English speaking ability viewed from students’ verbal aptitude. Keywords: Unmotivated students, Informational Gap Activity INTRODUCTION English becomes the most essential language in the world. Almost all the people from many different countries around the world use it to communicate. The area of English has always become a special interest. It is spoken by millions of people all over the world. Genc (2007, p. 6) says that